Do environmental factors lead to obesity? - ameneh marzban (Shahid Sadoughi University of Medical Sciences, 2021)
Weight gain is one of the problems that many people face and is unfortunately the fifth leading cause of death worldwide. Overweight is caused by many factors, such as the environment, family and genetic history, metabolism, unhealthy eating behavior or habits. Factors like family history are unchanging, but other factors, such as your habits, lifestyle and environmental factors can change (1). In the following article, a number of factors affecting overweight, such as Exposure to environmental toxins, Changes in the Microbiome, Chronic stress and cortisol and... will be discussed.